2019
DOI: 10.1038/s41415-019-1052-6
|View full text |Cite
|
Sign up to set email alerts
|

Health food blogger: friend or foe?

Abstract: Objectives: The Scientific Advisory Committee on Nutrition (SACN) and the World Health Organisation (WHO) have recently updated nutritional guidelines for a reduced sugar intake. With the increased popularity of online health-food bloggers and 'refined-sugar free' recipes, this review looked to analyse recipes from popular online bloggers to validate the veracity of their 'sugar-free' and 'healthy' claims and assess their adherence to recently implemented nutritional guidelines. Method: Four bloggers were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Rounsefell et al analyzed 26 original studies and found that social media engagement or exposure could be related to greater body dissatisfaction, dieting or restricting food, overeating, and choosing healthy foods among healthy young adults aged 18–30 [ 68 ]. Other authors pointed out that the advice given by so-called healthy food bloggers was not evidence-based and in the recipes analyzed by the authors, the fat content seemed to be increased to make up for the reduced sugar content [ 69 ]. Furthermore, some authors reported that messages posted on social media sites can promote health-damaging behavior, e.g., promoting anorexia [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rounsefell et al analyzed 26 original studies and found that social media engagement or exposure could be related to greater body dissatisfaction, dieting or restricting food, overeating, and choosing healthy foods among healthy young adults aged 18–30 [ 68 ]. Other authors pointed out that the advice given by so-called healthy food bloggers was not evidence-based and in the recipes analyzed by the authors, the fat content seemed to be increased to make up for the reduced sugar content [ 69 ]. Furthermore, some authors reported that messages posted on social media sites can promote health-damaging behavior, e.g., promoting anorexia [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sir, following several months of arduous editing I recently had the pleasure of having my research published in the BDJ. 1 Since publication, I have received upwards of a dozen emails from various journals and organisations asking me to chair their conferences and publish my work in their online journals for a waived fee. Upon receiving the first email I was elated, by the third suspicious and by the seventh utterly dismayed.…”
Section: Beware Predatory Journalsmentioning
confidence: 99%
“…The application criteria are clearly outlined on the person specifications, along with the points gained by meeting these criteria. 1 The process is highly competitive -in one specialty last year there were 120 applications for eight posts.…”
Section: How To Get Publishedmentioning
confidence: 99%